Positive youth development through taekwondo: a journey to the black belt - Lee, Y.; Lim, S. (Frontiers in Psychology, 2025)
Introduction: This study explored the role of Taekwondo (TKD) in fostering Positive Youth Developmental (PYD) outcomes among young practitioners. Drawing on the Sport-Based Youth Development (SBYD) framework, it investigated how the black belt journey contributes to physical, social, and emotional growth.